Improving of volumetric activity of the standard generator of technetium-99m; European Journal of Nuclear Medicine and Molecular Imaging; Vol. 43, suppl. 1 : European Association of Nuclear Medicine, EANM'16 - Rogov A. S. Alexander Sergeyevich; Skuridin V. S. Viktor Sergeyevich; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Nesterov E. A. Evgeny Alexandrovich; Sadkin V. L. Vladimir Leonidovich; Villa Pineda N. E. Nelson Enrrique; Ilyina E. A. Ekaterina Alekseevna (2016, 2016)
Title screen